Linguistic creativity as a feature of the text - Burska, Katarzyna; Cieśla, Bartłomiej (Linguistic creativity in marketing, 2022)
The article deals with the concept of linguistic creativity, behind which there are many meanings and research intuitions today. It may indicate: a) a dynamic process of creating an infinite number of statements on the basis of a finite number of linguistic signs and grammatical rules; b) linguistic and textual structures that are new or original; c) the ability to create artistic and functional texts as well as the products of such processes; d) linguistic image of the world created by the recipient, performativity of linguistic constructions; constructing the plot (and thus phenomena related to language, however, find expression mainly in the mental sphere); e) violation of the norm (ironic use)Therefore, the question arises, how to understand novelty or originality, relating both of these categories to the complex and extremely diverse linguistic matter? If we express the view that a text or some linguistic device is new or original - what exactly do we consider as the basis for comparison? This work is an attempt to indicate several research paths that can be derived from different ways of understanding the concept.